Extração enzimática de óleo e produção in situ de biodiesel a partir da Moringa oleífera Lam - Azevedo, Saulo Henrique Gomes de (2013)
With the growth and development of modern society, arises the need to search for new raw materials and new technologies which present the "clean" characteristic, and do not harm the environment, but can join the energy needs of industry and transportation. The Moringa oleifera Lam, plant originating from India, and currently present in the Brazilian Northeast, presents itself as a multi-purpose plant, can be used as a coagulant in water treatment, as a natural remedy and as a feedstock for biodiesel production. In this work, Moringa has been used as a raw material for studies on the extraction and subsequently in the synthesis of biodiesel. Studies have been conducted on various techniques of Moringa oil extraction (solvents, mechanical pressing and enzymatic), being specially developed an experimental design for the aqueous extraction with the aid of the enzyme Neutrase© 0.8 L, with the aim of analyzing the influence variable pH (5.5-7.5), temperature (45-55°C), time (16-24 hours) and amount of catalyst (2-5%) on the extraction yield. In relation to study of the synthesis of biodiesel was initially carried out a conventional transesterification (50°C, KOH as a catalyst, methanol and 60 minutes reaction). Next, a study was conducted using the technique of in situ transesterification by using an experimental design variables as temperature (30-60°C), catalyst amount (2-5%), and molar ratio oil / ethanol (1:420-1:600). The extraction technique that achieved the highest extraction yield (35%) was the one that used hexane as a solvent. The extraction using 32% ethanol obtained by mechanical pressing and extraction reached 25% yield. For the enzymatic extraction, the experimental design indicated that the extraction yield was most affected by the effect of the combination of temperature and time. The maximum yield obtained in this extraction was 16%. After the step of obtaining the oil was accomplished the synthesis of biodiesel by the conventional method and the in situ technique. The method of conventional transesterification was obtained a content of 100% and esters by in situ technique was also obtained in 100% in the experimental point 7, with a molar ratio oil / alcohol 1:420, Temperature 60°C in 5% weight KOH with the reaction time of 1.5 h. By the experimental design, it was found that the variable that most influenced the ester content was late the percentage of catalyst. By physico-chemical analysis it was observed that the biodiesel produced by the in situ method fell within the rules of the ANP, therefore this technique feasible, because does not require the preliminary stage of oil extraction and achieves high levels of esters